Genome-wide landscape of RNA-binding protein (RBP) networks as potential molecular regulators of psychiatric co-morbidities: a computational analysis - M. J. Nishanth; Shanker Jha (Egyptian Journal of Medical Human Genetics, 2023)
Abstract Background Psychiatric disorders are a major burden on global health. These illnesses manifest as co-morbid conditions, further complicating the treatment. There is a limited understanding of the molecular and regulatory basis of psychiatric co-morbidities. The existing research in this regard has largely focused on epigenetic modulators, non-coding RNAs, and transcription factors. RNA-binding proteins (RBPs) functioning as multi-protein complexes are now known to be predominant controllers of multiple gene regulatory processes. However, their involvement in gene expression dysregulation in psychiatric co-morbidities is yet to be understood. Results Ten RBPs (QKI, ELAVL2, EIF2S1, SRSF3, IGF2BP2, EIF4B, SNRNP70, FMR1, DAZAP1, and MBNL1) were identified to be associated with psychiatric disorders such as schizophrenia, major depression, and bipolar disorders. Analysis of transcriptomic changes in response to individual depletion of these RBPs showed the potential influence of a large number of RBPs driving differential gene expression, suggesting functional cross-talk giving rise to multi-protein networks. Subsequent transcriptome analysis of post-mortem human brain samples from diseased and control individuals also suggested the involvement of ~ 100 RBPs influencing gene expression changes. These RBPs were found to regulate various processes including transcript splicing, mRNA transport, localization, stability, and translation. They were also found to form an extensive interactive network. Further, hnRNP, SRSF, and PCBP family RBPs, Matrin3, U2AF2, KHDRBS1, PTBP1, and also PABPN1 were found to be the hub proteins of the RBP network. Conclusions Extensive RBP networks involving a few hub proteins could result in transcriptome-wide dysregulation of post-transcriptional modifications, potentially driving multiple psychiatric disorders. Understanding the functional involvement of RBP networks in psychiatric disorders would provide insights into the molecular basis of psychiatric co-morbidities.